Еthnodemographic factors of terrorist activity development in the Sudan-Sahel region - I. P. Suprunchuk; G. N. Zhirenko; A. A. Savchenko (Наука. Инновации. Технологии, 2025)
The article studies the countries of the Sudan-Sahel region and the processes of terrorism development on its territory. At the country level, an attempt is being made to study terrorist activity and the factors that cause it. The time frame of the study is the entire period of the independent existence of the countries of the region, dating back to the early 1960s. A number of socio-political problems and contradictions that form the current political instability and geostrategic significance of the Sudan-Sahel region have been identified. The paper examines in detail the influence of a group of ethnodemographic factors on terrorist activity. Their main aspects are the dynamics and type of reproduction of the population, the structure and features of settlement systems, the ethnic composition of the population and its mosaic. In addition, the genesis and development of socio-political conflicts in the countries of the Sahel region, determined by these factors, were analyzed. Based on the collected statistical data provided by the number of terrorist acts and their victims on terrorist activities in the countries of the Sudan-Sahel region, the article examines the dynamics of terrorism in the region, highlights the periods of its development, identifies the spatial and temporal shifts and changes that have occurred. The current place of the region in the global trends in the development of terrorism is determined, the leading countries, terrorist organizations and hotbeds of conflict affecting terrorism in the Sahel are identified. As part of the study of regional features of terrorist activity, using the cartographic method and spatial and temporal analysis tools, specific territorial centers of terrorism were identified, as well as terrorist clusters  – Chad, Central, Eastern, Coastal, Tuareg, Darfur and South Sudan.